Epithelial-Mesenchymal Transition Regulated by EphA2 Contributes to Vasculogenic Mimicry Formation of Head and Neck Squamous Cell Carcinoma. (17th April 2014) - Wang, Wei; Lin, Peng; Sun, Baocun; Zhang, Shiwu; Cai, Wenjuan; Han, Chunrong; Li, Li; Lu, Honghua; Zhao, Xiulan
Abstract : Purpose . Vasculogenic mimicry (VM) was related to invasion and metastasis of head and neck squamous cell carcinoma (HNSCC) patients. This study was designed to investigate the role of EphA2 in VM formation of HNSCC. Methods . The SiRNA technique was used to knock down the expression of EphA2 in vitro . The ability of cell migration and invasion were measured by transwell and wound healing assays; three-dimensional culture was used to detect the ability of channel-like structure formation; Western blot was used to detect the expression of epithelial-mesenchymal transition- (EMT-) related molecules in vitro . Further semiquantitative real-time RT-PCR assays and immunohistochemistry were used to demonstrate expression of EphA2 and EMT-related molecules according to VM presence or not in human tissue. Results . Knocking down EphA2 in vitro leads to disabled channel-like structure formation, reduction of invasion and migration ability, and reverse of EMT-related markers. Both semiquantitative real-time RT-PCR and immunohistochemistry showed that expressions of EphA2, Twist, and Vimentin were higher in the VM-positive group than in the VM-negative group significantly, while expressions of E-cadherin, claudin4, and DSG-3 were reverse. Conclusions . EphA2 played a key role in VM formation of HNSCC through regulation of EMT.